Effect of Biological Nitrogen Fertilizers on Improving the Quality of Maternal Wheat Chamran Seeds under water deficit - Navid Abbasi; Hamidreza Balouchi; Alireza Yadavi; Amin Salehi (علوم و فناوری بذر ایران)
In order to investigate the effect of water deficit stress and sources of nitrogen fertilizer on germination quality and vigor of wheat seeds of Chamran cultivar, an experiment was conducted in Agricultural Research Center of Fars province. In this experiment, wheat seeds were first treated at three levels of water deficit stress (complete irrigation, water deficit stress in milky and rough stage) and four levels of nitrogen fertilizer sources (urea fertilizer 100% plant requirement, urea fertilizer 25% Along with nitroxin and nitrogen, 50% urea fertilizer with nitroxin and nitrogen, 75% urea fertilizer with nitroxin and nitrogen were produced. Then, the quality and vigor of the seeds were tested in two standard experiments of germination and accelerated aging in a factorial design with four replications. The results showed that the effect of experimental treatments on all measured traits except germination percentage was significant. Water deficit stress and sources of nitroxin and nitrogen fertilizer with 25% urea at the beginning of decline led to an increase in protein concentration (12.39%), but the lowest amount of starch (20.85 %) under the interaction of nitroxin and nitrogen fertilizer with 75% urea in 48 hours Deterioration was observed. Water deficit stress also increased the concentration of soluble sugars and decreased the grain alpha-amylase enzymes. Overall, the results of this study showed that the use of combined treatments of urea fertilizer and biofertilizers in stress conditions to feed the mother plant led to the production of seeds with higher vigor and more resistance to decay.